2017
DOI: 10.1038/ncomms16041
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of macrophage activation as disease-relevant phenotype predictive of inflammation and cancer survival

Abstract: Although mouse models exist for many immune-based diseases, the clinical translation remains challenging. Most basic and translational studies utilize only a single inbred mouse strain. However, basal and diseased immune states in humans show vast inter-individual variability. Here, focusing on macrophage responses to lipopolysaccharide (LPS), we use the hybrid mouse diversity panel (HMDP) of 83 inbred strains as a surrogate for human natural immune variation. Since conventional bioinformatics fail to analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 58 publications
(101 reference statements)
1
63
2
Order By: Relevance
“…When aggregated together, the mouse model predictions of human sepsis pathways increased in total coverage, but tended to be less precise. This runs contrary to observations that including multiple mouse strains in an experiment and using the increased heterogeneity of the mouse cohort as a surrogate for human disease heterogeneity improved translation of insights from mouse models to human context (29). In the context of the ssANN, increasing the heterogeneity of the mouse cohort in the training set by inclusion of multiple strains resulted in better predictions than when the ssANN was trained on individual mouse sepsis strains, particularly when the human cohort being predicted was itself heterogeneous (Figure 3b).…”
Section: Discussioncontrasting
confidence: 58%
“…When aggregated together, the mouse model predictions of human sepsis pathways increased in total coverage, but tended to be less precise. This runs contrary to observations that including multiple mouse strains in an experiment and using the increased heterogeneity of the mouse cohort as a surrogate for human disease heterogeneity improved translation of insights from mouse models to human context (29). In the context of the ssANN, increasing the heterogeneity of the mouse cohort in the training set by inclusion of multiple strains resulted in better predictions than when the ssANN was trained on individual mouse sepsis strains, particularly when the human cohort being predicted was itself heterogeneous (Figure 3b).…”
Section: Discussioncontrasting
confidence: 58%
“…Indeed, when we examined the FBR of monocytes derived from three different donors, it was found that, interestingly, different individuals exhibited varying degrees of immune responses to the same Ti microbeads (Figure d). While two donors (Donors B and C) did not exhibit noticeable difference in M1/M2 differentiation of their PBMC‐derived monocytes, one donor (Donar A) had strong pro‐inflammatory reaction to the Ti microbeads (Figure e,f), clearly indicating that there is likely a “population spectrum” of responses to the same implant possibly due to differences in receptor expressions and cytokine profiles of the immune cells . It should be noted that, this dataset achieved with human primary monocytes from healthy donors was different from that observed when human THP‐1 monocyte cell line was used (which always showed pro‐inflammatory phenotype).…”
Section: Parameters and Constants Used For Modelingmentioning
confidence: 78%
“…None of the existing approaches allow for personalized screening of the FBR to implants. Indeed, literature suggests a significant level of inter‐individual variation that is driven by individual's immunological profile. Therefore, there is a strong need for personalized assessment of FBR at low cost and in a higher‐throughput/rapid manner to select the most suitable implant material with optimal parameters, for a given patient.…”
Section: Parameters and Constants Used For Modelingmentioning
confidence: 99%
“…However, these often fail to capture the underlying biological structure 13,14 because most correlations are non-linear 15,16 . Recently, we described heterogeneity in macrophage polarization by correlating population variability with the expression of known relevant genes 17 . This approach still requires user input (the relevant genes).…”
Section: Introductionmentioning
confidence: 99%
“…It uses pre-processing filters, t-SNEbased dimensionality reduction, and intuitive visualizations (including movies) for analysis of co-expressed networks of genes. Unlike previous approaches 17 , PRESTO is hypothesis-free and processes all data while blind to sample designation. We demonstrate the usefulness of the tool for exploring co-expressed biological pathways in published pre-clinical data as well as valuable diagnostic signatures from clinical data.…”
Section: Introductionmentioning
confidence: 99%